Effects of inflation on the coupling between the ribs and the lung in dogs - Troyer, André De; Leduc, Dimitri (The Journal of physiology, 2004)
The coupling between the ribs and the lung in dogs increases with increasing rib number in the cranial part of the rib cage and then decreases markedly in the caudal part. The hypothesis was raised that this non-uniformity is primarily related to differences between the areas of the lung subtended by the different ribs, and in the current study we tested this idea by assessing the effects of passive lung inflation. Thus, by causing a descent of the diaphragm, inflation would expand the area of the lung subtended by the caudal ribs and improve the coupling between these ribs and the lung. The axial displacements of the ribs and the changes in airway opening pressure (Î P ao ) were measured in anaesthetized, pancuronium-treated, supine dogs while loads were applied in the cranial direction to individual rib pairs at functional residual capacity (FRC) and after passive inflation to 10 and 20 cmH 2 O transrespiratory pressure. In agreement with the hypothesis, inflation caused an increase in Î P ao for ribs 9 and 10. The most prominent alteration, however, was a marked decrease in Î P ao for ribs 2â8; at 20 cmH 2 O, Î P ao for these ribs was only 30% of the value at FRC. Additional measurements indicated that this decrease in Î P ao results partly from the increase in diaphragmatic compliance but mostly from the reduction in outward rib displacement. This alteration in the pattern of rib motion should add to the decrease in muscle length to reduce the lung expanding action of the external intercostal muscles at high lung volumes.